APPLICATION OF PROBLEM BASED LEARNING (PBL) WITH MODEL MATERIALS TO IMPROVE MATHEMATICS ABOUT SOLID FIGURES TO FIFTH GRADE STUDENTS OF SDN 1 DANASRI IN ACADEMIC YEAR OF 2019/2020 - TYA DWI AGUSTIN; WAHYUDI WAHYUDI; NGATMAN NGATMAN (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
Abstract:The study aimed: (1) to describe the steps of PBL with model materials, (2) to improve mathematics, and (3) to describe the constraints and solutions. It was a collaborative classroom action research (CAR) carried out in three cycles. Each cycle consisted of planning, implementation, observation, and reflection. The subjects were teachers and 20 students. Data collection techniques used observation, interviews, and tests. Data analysis included data reduction, data presentation, and drawing conclusions. The results showed that: (1) the steps to the application of PBL with model materials to improve mathematics about solid figures to fifth grade students of SD Negeri 1 Danasri in academic year of 2019/2020 were: (a) examining problem orientation with the model materials, (b) preparing the students to work in groups, (c) having the students to investigate individually or in groups with the help of model materials, (d) having presentation and discussion by using model materials; (e) analyzing and evaluating  problem solving process with the help of model materials; (2) the application of PBL with model materials improved mathematics about solid figures. The average percentages of mastery learning were 85% in the first cycle, 90% in the second cycle, and 95% in the third cycle: (3) obstacles in each meeting were (a) a few students used the model materials as tools while learning process and having group discussions, (b) a few students asked questions. The solutions were: (a) the teacher introduced the model materials, (b) the teacher stimulated the students to ask questions.